2019
DOI: 10.1016/j.compgeo.2019.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Ability of a pore network model to predict fluid flow and drag in saturated granular materials

Abstract: The local flow field and seepage induced drag obtained from Pore Network Models (PNM) is compared to Immersed Boundary Method (IBM) simulations, for a range of linear graded and bimodal samples. PNM were generated using a weighted Delaunay Tessellation (DT), along with the Modified Delaunay Tessellation (MDT) which considers the merging of tetrahedral Delaunay cells. Two local conductivity models are compared in simulating fluid flow in the PNM. The local pressure field was very accurately captured, while the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…These observations on the transient evolution of the porosity distribution demonstrates the capability of spatial TDR to make physical observations of the mixing process in filtration experiments from onset to progression. Ongoing research aims to employ these physical observations for calibration of numerical particle-scale simulations of the filtration process using coupled computational fluid mechanics and discrete element method (Smith et al, 2020;Che et al, 2021) and pore network models (van der Linden et al, 2018;Sufian et al, 2019). These physical observations can also be applied to large deformation models employing smooth particle hydrodynamic or the material point method.…”
Section: Discussionmentioning
confidence: 99%
“…These observations on the transient evolution of the porosity distribution demonstrates the capability of spatial TDR to make physical observations of the mixing process in filtration experiments from onset to progression. Ongoing research aims to employ these physical observations for calibration of numerical particle-scale simulations of the filtration process using coupled computational fluid mechanics and discrete element method (Smith et al, 2020;Che et al, 2021) and pore network models (van der Linden et al, 2018;Sufian et al, 2019). These physical observations can also be applied to large deformation models employing smooth particle hydrodynamic or the material point method.…”
Section: Discussionmentioning
confidence: 99%
“…Taylor et al (2017)) or the conductance that governs flow in an individual pore throat (e.g. Sufian et al (2019)). As discussed below, homogenization approaches can be applied.…”
Section: Sub-pore Scale -Numerical Modelsmentioning
confidence: 99%
“…Partitioning is non-trivial as the void space is continuous and no partitioning algorithm can be wholly objective. For example, Sufian et al (2019) compare PNMs obtained using slightly different approaches to partitioning.…”
Section: Pore Network Modelsmentioning
confidence: 99%
“…In contrast to solving the elliptic Navier-Stokes equations on the void space using FEM, immersed boundary methods, or lattice-Boltzmann methods, solving the PNM can be done with simple Gauss-Seidel over relaxation [16] and conservation of mass, or a solution to a system of linear equations with nodal analysis. Sufian et al [41] showed that the PNMs accurately predict the drops in pressure between pores when compared to numerical solutions of the Navier-Stokes equations. Gackiewicz et al [15] also showed that PNMs computed with the maximum-ball and Delaunay method agreed with FEM solutions to the Navier-Stokes equations for sphere packed materials.…”
Section: Related Workmentioning
confidence: 99%